Rational expectations and business forecasts of Malaysian Firms - Chong, Lucy Lee Yun (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The irrational behavior observed in recent studies raises the issue about the achievability on rationality. Accordingly, this study intended to examine whether or not, the employment, capital expenditure, and gross revenue expectations, of which that are formed by the Malaysian business firms from the nine individual sectors and a total sector, are significantly in accordance with the Rational Expectations Hypothesis (REH). The survey expectational data of the Business Expectations Survey of Limited Companies that is published by the Department of Statistics Malaysia, and the information sets series taken from the International Financial Statistics, International Monetary Fund as well as Quarterly Economic Bulletin, Bank Negara Malaysia, on the utmost period of 1978:1 to 2010:1, are utilized for the estimations of this study. The analyses are estimated by using integrational tests, Johansen-Juselius cointegration test, rationality tests and diagnostic tests. The findings demonstrated that just five out of 30 series acted in line with the REH, while the rest are found to either hold for irrationality or undetermined. Besides, the I(0) data are more likely to fail in comforting the REH, but the I(1) data are contrariwise. Moreover, the services sectors are shown to perform better than the agricultural and industrial sectors, in serving as the rational agents to their expectations. In addition, this study indicated that the gross revenue expectations are in the position of obeying to the REH the most when the macro series have been applied and vice versa. Also, the firms are shown to be pessimistic all the way in predicting the gross revenue without the usage of macro series. Lastly, this study illustrated that the aggregated data are not prone to be rational as mentioned by pioneer studies, instead, it added to the latter studies which remarked that the diverse nature of the individual firms could make for a deeper contrast to the REH at the aggregated level. Thus, the government is recommended to conduct the policies that are capable in aiding the irrational business players, while with less intervention to the rational business players, with extra caution.